If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=6(x-6)
We move all terms to the left:
42-(6(x-6))=0
We calculate terms in parentheses: -(6(x-6)), so:We get rid of parentheses
6(x-6)
We multiply parentheses
6x-36
Back to the equation:
-(6x-36)
-6x+36+42=0
We add all the numbers together, and all the variables
-6x+78=0
We move all terms containing x to the left, all other terms to the right
-6x=-78
x=-78/-6
x=+13
| -7v-1=-8v-8 | | -9z-1=26 | | 17=x/4-17 | | 28=y+9 | | n=6X35+ | | m/5+4=21 | | (0.7+x)/(6+x)=0.05 | | 11x+3=5x+9 | | p3=100 | | 7m+4=7-2m+8m | | -6s+8=8+2s+10s | | -9-2z=7-z-6 | | 6.5m=-17 | | z-592=1209 | | 2w^2+8-64=0 | | Y=-a+5 | | 2t-6=-t-3 | | 3x-7+9=5x-2x | | h-6=4+9 | | x-67=88 | | -+3q=9q | | z+34=-17 | | 15-2v=v | | 200m-100m+52,800=55,825-175m | | a+12.5=3 | | 10x-15=135 | | f+-4=8 | | 20x+21=2x-3 | | 2/3x+1/6=3/4x1 | | 4.9g+9=1.9g+21 | | -9-3D=10d-10d+9 | | g-45=-72 |